1998
DOI: 10.3354/meps165145
|View full text |Cite
|
Sign up to set email alerts
|

Diel movements of juvenile plaice Pleuronectes platessa in relation to predators, competitors, food availability and abiotic factors on a microtidal nursery ground

Abstract: The distribution and movements of juvenile plaice Pleuronectes platessa and their potential predators and competitors were recorded in a small microtidal (-20 cm) bay on the west coast of Sweden uslng underwater television and conventional nettlng techniques. There was generally close correspondence between the results obtalned by the 2 methods. Young plaice moved upshore at dusk and returned to deeper water at dawn. Larger predatory fishes also moved upshore at night but not as far as the plaice; they also en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(69 citation statements)
references
References 24 publications
5
61
1
2
Order By: Relevance
“…Crangon crangon and Carcinus maenas have both been shown experimentally to be more active nocturnally (Naylor 1958, Kitching et al 1959, Hagerman 1970, Dyer & Uglow 1978, van Donk & de Wilde 1981, and, in underwater television observations in the same area as this study, both species were seen more at night than during the daylight (Burrows et al 1994). In contrast, on a microtidal beach in Sweden, C. crangon were mostly active during the day while C. maenas were nocturnally active, with neither species showing migration (Gibson et al 1998). Abello et al (1991) found that Liocarcinus depurator were most active at night, but, contrary to the present observations, L. holsatus were most active during the day.…”
Section: Die1 Movementscontrasting
confidence: 56%
“…Crangon crangon and Carcinus maenas have both been shown experimentally to be more active nocturnally (Naylor 1958, Kitching et al 1959, Hagerman 1970, Dyer & Uglow 1978, van Donk & de Wilde 1981, and, in underwater television observations in the same area as this study, both species were seen more at night than during the daylight (Burrows et al 1994). In contrast, on a microtidal beach in Sweden, C. crangon were mostly active during the day while C. maenas were nocturnally active, with neither species showing migration (Gibson et al 1998). Abello et al (1991) found that Liocarcinus depurator were most active at night, but, contrary to the present observations, L. holsatus were most active during the day.…”
Section: Die1 Movementscontrasting
confidence: 56%
“…Shore crabs are most abundant at depths of > 2 m during the day, although they are shallower and more abundant at night (Ansell et al 1999). Overlap between this predator and the smallest plaice is therefore low, and any diel changes in the distribution of crabs is matched by those of the plaice (Burrows et al 1994, Gibson et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, crepuscular periods represent a less favourable period for diurnal individuals, whose vision is not adapted to dim light conditions. This especially concerns young and smallsized individuals, which are exposed to a greater predation pressure than older and bigger fi sh (Helfman 1981, Gibson et al 1998). An increased activity of larger and older individuals later in the evening compared to smaller fi sh could also be related to a diet shift, as observed in lakes (Helfman 1981).…”
Section: Temporal Patterning Of Abundances and Behavioursmentioning
confidence: 99%